Comparative Analysis of Maternal Neutrophils, Age, and Parity in PROM and Prolonged Labor - Fony; Asih Luklu Susiati; Wahyuni Hafid; Hardianti, H.P Alam; Trinarti Senolangi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Premature Rupture of Membranes (PROM) and prolonged labor remain significant obstetric problems associated with maternal inflammatory responses and adverse perinatal outcomes. Differences in neutrophil activation between these two conditions may reflect distinct inflammatory mechanisms. This study aimed to compare maternal neutrophil levels, age, and parity in PROM and prolonged labor cases. A comparative analytic design with a cross-sectional approach was conducted at RSIA Sitti Khadijah 1 Makassar involving 50 postpartum women who met the inclusion criteria. Data were collected through structured interviews and hematological examination of maternal blood samples. The results show that maternal neutrophil levels differed significantly between PROM and prolonged labor groups. The mean neutrophil level was higher in prolonged labor (82.44 ± 7.008 mg/L) than in PROM (75.10 ± 9.525 mg/L), with a significant p-value of 0.004. Abnormal neutrophil levels were predominantly observed in prolonged labor across all age and parity categories, especially among primiparous women. In contrast, PROM cases showed more varied neutrophil patterns, with a greater proportion of normal values in multipara. These findings suggest that prolonged labor is more strongly associated with heightened maternal inflammatory responses. Maternal neutrophil levels may serve as a practical clinical indicator to distinguish inflammatory status and support early risk assessment in obstetric management.